2021
DOI: 10.1088/1361-6579/ac1497
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between heated environment and active standing test on cardiovascular autonomic control in healthy individuals

Abstract: Objective. To investigate the interplay between active standing and heat stress on cardiovascular autonomic modulation in healthy individuals. Approach. Blood pressure (BP) and ECG were continuously recorded during 30 min in supine (SUP) and 6 min in orthostatic position (ORT) under thermal reference (TC; ∼24 °C) or heated environment (HOT; ∼36 °C) conditions, in a randomized order. All data collection was performed during the winter and spring seasons when typical outdoor temperatures are ∼23 °C. Spectral ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…The axillary (Tax), tympanic (Ttym), and sublingual (Tsub) temperature increased in heated conditions compared to thermal reference conditions (Yamamoto et al 2007). Ferreira et al (2021) found an increment of 1.6 °C in Tskin, and Carrillo and colleagues (2016) reported an increment of ∼0.8 °C in participants' body temperature compared to a thermal neutral condition. One study described that the internal temperature increased up to 36.8 °C and 37.1 °C after 40 and 115 min of the heating protocol, respectively (Brenner et al 1997).…”
Section: Body Temperaturementioning
confidence: 98%
See 4 more Smart Citations
“…The axillary (Tax), tympanic (Ttym), and sublingual (Tsub) temperature increased in heated conditions compared to thermal reference conditions (Yamamoto et al 2007). Ferreira et al (2021) found an increment of 1.6 °C in Tskin, and Carrillo and colleagues (2016) reported an increment of ∼0.8 °C in participants' body temperature compared to a thermal neutral condition. One study described that the internal temperature increased up to 36.8 °C and 37.1 °C after 40 and 115 min of the heating protocol, respectively (Brenner et al 1997).…”
Section: Body Temperaturementioning
confidence: 98%
“…head-up tilt and active standing tests) were incorporated in our assessment. Indeed, autonomic maneuvers are commonly employed to confirm the physiological meaning of HRV indexes (Montano et al 1994, Rodrigues et al 2019, which seems to clarify the selective contribution of the autonomic nervous system (ANS) to the heart during heat stress (Ferreira et al 2021).…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations